2004
DOI: 10.1063/1.1839287
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission study of energy-band alignment for RuOx∕HfO2∕Si system

Abstract: Conductive oxides RuOx as alternative electrode on high-κ HfO2 gate dielectric have been fabricated by ultrahigh-vacuum sputtering and subsequently oxidized using oxygen plasma. The energy-band alignment for the RuOx∕HfO2∕Si system and the oxidation-state dependence of barrier height for RuOx contacting to HfO2 dielectrics has been analyzed by x-ray photoemission spectroscopy. The valence- and conduction-band offsets of HfO2∕Si are determined to be 3.05±0.1 and 1.48±0.1eV, respectively. The barrier heights for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 25 publications
5
14
0
Order By: Relevance
“…The Si 2p core-level spectra were used as a reference to determine the valence band offset of HfO 2 film relative to Si substrate. The leading edge of valence band spectrum for n-type Si substrate was at 0.60 eV in our previous report 14 and was also confirmed in the present work. Then the energy difference between Si 2p centroids and the leading edge of Si valence band spectra is 99.50− 0.60 = 98.90 eV, in good agreement with the report of Chamber et al with the values of 98.90 and 98.98 eV for n-and p-Si, respectively.…”
supporting
confidence: 90%
“…The Si 2p core-level spectra were used as a reference to determine the valence band offset of HfO 2 film relative to Si substrate. The leading edge of valence band spectrum for n-type Si substrate was at 0.60 eV in our previous report 14 and was also confirmed in the present work. Then the energy difference between Si 2p centroids and the leading edge of Si valence band spectra is 99.50− 0.60 = 98.90 eV, in good agreement with the report of Chamber et al with the values of 98.90 and 98.98 eV for n-and p-Si, respectively.…”
supporting
confidence: 90%
“…23-25 and 34-38͒ and even that of RuO 2 ͑5.0− 5.3 eV͒. [35][36][37][38][39][40][41][42] However, the large WF shift corresponds very well with Nabatame et al's report, 22 which shows a V fb shift of ϳ1 V for both Ru/ SiO 2 and Ru/ HfO 2 gated stacks after thermal treatment in O 2 .…”
Section: E Dependence On the Type Of Dielectricssupporting
confidence: 83%
“…The idea is based on the fact that the layer in contact with the gate dielectric is critical to set the WF of metal gates. It is widely reported that RuO x has a higher WF than Ru does, [35][36][37][38]44,45 and it is also known that oxygen adsorption at the Ru outer surface can increase its WF. 34,46 It is possible that the formation of a thin interfacial RuO x layer will lead to a higher WF and the shift of the V fb .…”
Section: A Proposed Mechanisms Of the V Fb Shiftmentioning
confidence: 99%
“…6,9 The measurement of the band offsets in a HfO 2 / SiO 2 / Si stack has received much attention over the past decade because the band offsets are directly related to the gate leakage current for thin oxide stacks. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] The primary methods that have been used for this characterization are x-ray, soft x-ray, UV, and inverse photoelectron spectroscopies ͑XPS, SXPS, UPS, and IPS, respectively͒, internal photoemission ͑IPE͒, and ballistic electron energy spectroscopy ͑BEES͒. The reported values for the HfO 2 -Si valence band offset ͑VBO͒ span a range from 2.5 to 3.4 eV.…”
Section: Introductionmentioning
confidence: 96%
“…13,14,16,20,21 These XPS based measurements of the HfO 2 -Si VBO did not, however, take the effect of sample charging into account. In this study, we have measured the HfO 2 -Si VBO while taking sample charging into account, and have obtained values that are in closer agreement with those on the lower end of the range of published VBO values.…”
Section: Introductionmentioning
confidence: 97%